Membangun Jiwa Kewirausahaan dengan Kegiatan Unggulan Koperasi Mahasiswa UNY Mengembangkan Potensi Mahasiswa di Berbagai Bidang - Fastiani, Afria Eky; Rahmadani, Nurulita Fina; Wijayanti, Agustina Tri; Dhewantoro, Happri Novriza Setya (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
Student cooperatives, as a member-based economic  forum,  which  not only meets the daily needs of students, but student cooperatives can be a mini laboratory for prospective entrepreneurs. However, in carrying out its operations, student cooperatives  are  often  faced  with  various obstacles.  This  research  will  reveal how student cooperatives can be an effective means to foster the  entrepreneurial  spirit  of  students,  as well as identify the challenges.